LPCAT1 enhances castration resistant prostate cancer progression via increased mRNA synthesis and PAF production. - Chao Han; Guopeng Yu; Yuanshen Mao; Shangqing Song; Long Li; Lin Zhou; Zhong Wang; Yushan Liu; Minglun Li; Bin Xu (PLoS ONE, 2020)
Our previously study shown that Lysophosphatidylcholine Acyltransferase1 (LPCAT1) is overexpressed in castration resistant prostate cancer (CRPC) relative to primary prostate cancer (PCa), and androgen controls its expression via the Wnt signaling pathway. While highly expressed in CRPC, the role of LPCAT1 remains unclear. In vitro cell experiments referred to cell transfection, mutagenesis, proliferation, migration, invasion, cell cycle progression and apoptosis, Western blotting, Pulse-chase RNA labeling. BALB/c nude mice were used for in vivo experiments. We found that LPCAT1 overexpression enhanced the proliferation, migration, and invasion of CRPC cells both in vitro and in vivo. Silencing of LPCAT1 reduced the proliferation and the invasive capabilities of CRPC cells. Providing exogenous PAF to LPCAT1 knockdown cells increased their invasive capabilities; however platelet activating factor acetylhydrolase (PAF-AH) and the PAFR antagonist ABT-491 both reversed this phenotype; proliferation of CRPC cells was not affected in either model. LPCAT1 was found to mediate CRPC growth via nuclear re-localization and Histone H4 palmitoylation in an androgen-dependent fashion, increasing mRNA synthesis rates. We also found that LPCAT1 overexpression led to CRPC cell resistance to treatment with paclitaxel. LPCAT1 overexpression in CRPC cells drives tumor progression via increased mRNA synthesis and PAF production. Our results highlight LPCAT1 as a viable therapeutic target in the context of CRPC.